PURA NEGARA GAMBUR ANGLAYANG, KECAMATAN KUBUTAMBAHAN, BULELENG (PERSPEKTIF PARIWISATA DAN KOMUNIKASI PLURALISME) - I Putu Mardika (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2018)
This article examines the history of the Gambur Anglayang State Temple in terms of Pluralism and religious tourism. The research was conducted in Kubutambahan village, district of Kubutambahan, Buleleng, Bali. Search informants determined by purposive sampling. Determination informant begins with determining the key informants, and then developed using a chain with sampling. This technique called snowball technique. For data analysis, among others: (1) the determination of the informant, (2) collecting data, (3) the validity of the data, (4) data analysis, ( 5) conclusions / verification. Negara Gambur Anglayang temple established in 1260 or the 13th century by people around Kuta Banding beach in the reign of King Bhatara Parameswara (2) The structure of Negara Gambur Anglayang temple consists of three pages or mandala the part is Nista Mandala (outside), Madya Mandala (middle side), and Utama Mandala (inside). Vertically shrine at Negara Gambur Anglayang temple refers to the concept that consists Triangga (feet, body, and head) that apply in the Negara Gambur Anglayang temple. It is shown from the pelingih-pelinggih line that represents different religions and ethnicities. For example Bhatara Ratu Gede Siwa Rambut Sedana, Bhatara Sri Dwijendra Ratu Agung Dalem Makkah (Islam), Ratu Agung Syahbandar (China) are Dewa Pabean (Pelabuhan), Ratu Agung Melayu (ethnic Malays), and Ratu Bagus Nganten (Ratu Bagus Sundawan) from Sundanese West Java. Keywords: Pura, Tourism, Pluralism